PENATALAKSANAAN FISIOTERAPI PADA KASUS DUCHENNE MUSCULAR DSYTROPHY POST OPERASI TENDON ACHILLES BILATERAL DENGAN MODALITAS ULTRASOUND DAN TERAPI LATIHAN DI RSUD BANDUNG KIWARI - Sidik, Kurnia; Thesalonika, Lona; Rahman, Ika (Jurnal Infokes, 2023)
Duchenne Muscular Dystrophy (DMD) is one of the most common genetic neuromuscular diseases that occur in children, particularly in boys. This condition is characterized by progressive weakness of skeletal muscles caused by mutations in the gene encoding the dystrophin protein. Such mutations lead to a gradual decline in motor abilities, including walking, standing, and climbing stairs. Over time, DMD may also affect cardiac and respiratory functions, resulting in a significant decrease in the patient’s quality of life. This case aims to determine the physiotherapy management in reducing pain, maintaining muscle strength, and preserving the range of motion in a patient with Duchenne Muscular Dystrophy using ultrasound modalities and isotonic–isometric exercise therapy. The exercises administered included bridging, hip extension, hip march, straight leg raises, side-lying hip abduction, standing hip abduction, and side-lying hip adduction. After six physiotherapy sessions, there was a decrease in pain on pressure from T1: 4 to T6: 3 and in movement pain from T1: 3 to T6: 2. Muscle strength showed relatively stable results, with hip flexion T1=3 to T6=3-, hip extension T1=2 to T6=2-, hip abduction T1=3 to T6=3-, and hip adduction T1=2+ to T6=2. The range of motion remained stable, with left ankle dorsiflexion T1: 10° to T6: 9° and plantarflexion T1: 35° to T6: 34°. Functional activity assessment using the NSAA showed a stable score of 20 from T1 to T6.